Combating Corruption Offenses: Foreign Experience, Theoretical, Practical, Legal Regulations, and Improvement - Leheza, Yevhen; Kulinich , Olha; Zhuravlova , Tetiana; Khainatskyi , Yevhen; Sainchyn , Serhiy (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2025)
This research explores preventative strategies, law enforcement frameworks, and the pivotal roles of specialized anti-corruption agencies, alongside the vital component of international collaboration using a global approach in combating corruption crimes, by examining successful strategies implemented in various countries. A closer look will be given to the methodologies used in Singapore, Hong Kong, the United Arab Emirates, Saudi Arabia, Malaysia, Indonesia, and Northern European countries, with an emphasis on practical takeaways that can refine Ukraine's own anti-corruption initiatives. An examination of successful international practices reveals that effective anti-corruption efforts must begin with robust preventive strategies designed to limit opportunities for corruption. These foundational elements include: increased transparency and openness within government operations; comprehensive reform of public administration and human resource management; utilizing digitalization to reduce human involvement; effective management of conflicts of interest and ethical codes; and providing adequate protection for whistleblowers. Furthermore, tackling corruption, particularly in its transnational forms, requires active international collaboration. Critical to this endeavor are instruments such as mutual legal assistance, extradition agreements, and the exchange of intelligence among international law enforcement agencies (illustrated by collaborative efforts within organizations like Europol and Interpol).